-13k=19-14k

Simple and best practice solution for -13k=19-14k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13k=19-14k equation:


Simplifying
-13k = 19 + -14k

Solving
-13k = 19 + -14k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '14k' to each side of the equation.
-13k + 14k = 19 + -14k + 14k

Combine like terms: -13k + 14k = 1k
1k = 19 + -14k + 14k

Combine like terms: -14k + 14k = 0
1k = 19 + 0
1k = 19

Divide each side by '1'.
k = 19

Simplifying
k = 19

See similar equations:

| f/5=8 | | 0=2y-y | | 8/4=/16/x | | 34=6s-8s | | 4c-1=11 | | -12h+13.64=-8.64-13.3h | | -2-19+n=7 | | 3(x+4)=5x-12-2x | | 5+2p-2=7p+27-2p | | 50m+20m+5m=-100 | | 4y+3=x-4 | | 4+3x=-4(x-8) | | 15p+13q+p-8q-7p= | | 39=3(c+6) | | 1000x=40000 | | X+10-8+2=10 | | 4x+4(x+3)=36 | | 12x+9y=360 | | -20=5+7(y+9) | | 4.5x-40.5=13.5 | | 2a+5a-13=50 | | -2v+8=8+3v | | 27y-3y+6y=30 | | 6y-2=3 | | (6x+3)(x+5)=(2+x)(6+2x)-4 | | 3+6p=63 | | -6+5s=-71 | | -7+3y=-22 | | -6x-21=-141 | | 3X^2/20 | | 27=6d+9 | | 8x+5y+3x-2y= |

Equations solver categories